The relationship between exposure to domestic violence, victim blaming and aggressive behaviour among Malaysian adolescents - Azlina binti Amir Kassim (Kulliyyah of Islamic Revealed Knowledge and Human Science, International Islamic University Malaysia, 2012)
Domestic violence is a pervasive social ill worldwide and the adverse effects on adolescents' behaviour have been widely documented. In Malaysia, literature on domestic violence especially wife battering has been documented but no correlational study related to domestic violence and adolescents' aggressive behaviour has been cited. Therefore, this research focuses on exploring the relationships between exposure to domestic violence, victim blaming and aggressive behaviour among Malaysian adolescents. The study examines I) the relationship between level of exposure to domestic violence and level of aggressive behaviour among adolescents, 2) the relationship between victim blaming and the level of aggressive behavior among adolescents, 3) the level exposure to domestic violence and level of victim blaming as predictors in the level of aggressive behavior among adolescents, and 4) the mediating effect of victim blaming on the relationship between exposure to domestic violence and level of aggressive behaviour among adolescents. The sample consisted of280 adolescents (mean age= 16.31) from two Malaysian public schools The measurements used in this study were Child Exposure to Domestic Violence Scale (CEDV) (Edleson, Shin & Johnson, 2008), Domestic Violence Myth Acceptance Scale (DVMAS) (Peters, 2003) and Aggression Questionnaire (Buss & Perry, 1992). Bivariate correlations reveal a significant relationship between exposure to domestic violence and level of aggressive behaviour, r =.24, p= O.oi; and between victim blaming and the level of aggressive behaviour, r =.29, p=O.Ol. Multiple regression analysis reveal that after controlling the effects of socio-demographic variables, exposure to domestic violence and victim blaming accounted to an additional II% of variance in the level of aggressive behaviour, R2 change = 0.11, F (1, 269) = 5.80,p = O.oi. Lastly, results indicate that victim blaming did not mediate the relationship between exposure to domestic violence and aggressive behavior.